Non-Edible Seeds for the Production of Biodiesel - Adhikari, Suraj Raj; Baral, Sunil Dutta; Pokhrel, Kusum (Himalayan Biodiversity, 2020)
The global energy demand is increasing day by day. The consumption of the fuel, as well as the demand, is expected to grow rapidly and use of fossil energy is causing harmful impacts on the environment. Biofuels are attractive alternative to petroleum diesel derived from a variety of feedstocks, vegetable oils, animal fats, and waste cooking oil. They are renewable, non-toxic and biodegradable. At present, biodiesel is mainly produced from many edible oils seed. The extensive use of edible oils for production of biodiesel may lead to food crisis. Therefore, production of biodiesel from non-edible oils is a successful method to overcome all the related problems with edible oils.